2005
DOI: 10.1093/rheumatology/keh557
|View full text |Cite
|
Sign up to set email alerts
|

Joint hypermobility syndrome in childhood. A not so benign multisystem disorder?

Abstract: JHS is poorly recognized in children with a long delay in the time to diagnosis. Although there is a referral bias towards joint symptoms, a surprisingly large proportion is associated with significant neuromuscular and motor development problems. Our patients with JHS also show many overlap features with genetic disorders such as EDS and Marfan syndrome. The delay in diagnosis results in poor control of pain and disruption of normal home life, schooling and physical activities. Knowledge of the diagnosis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
306
3
13

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(333 citation statements)
references
References 22 publications
11
306
3
13
Order By: Relevance
“…Testing of the BS was performed in school's environment. As it has been noted in the study of Adib et al [1], half of JHS patients have been missing school. It could hide some part of those patients.…”
Section: Discussionmentioning
confidence: 62%
“…Testing of the BS was performed in school's environment. As it has been noted in the study of Adib et al [1], half of JHS patients have been missing school. It could hide some part of those patients.…”
Section: Discussionmentioning
confidence: 62%
“…This is perhaps because this is a primarily young population that does not include either children or the elderly population. Previous studies of JHS suggest a trend toward decreasing prevalence of the disorder with increasing age [1,13,24].…”
Section: Discussionmentioning
confidence: 82%
“…For this reason, and because of its tendency to be overlooked as a benign disorder, several authors believe JHS is frequently misdiagnosed and more prevalent than is suggested by the current literature [1,18].…”
Section: Discussionmentioning
confidence: 98%
“…Those with the condition report generalized joint hypermobility and symptoms like musculoskeletal complaints, recurrent joint dislocations/joint instability and chronic pain, sometimes starting in childhood (Adib, Davies, Grahame, Woo, & Murray, 2005; Clinch & Ecclestone, 2009; Malfait et al, 2017). Physiotherapy is considered to be the main mode of treatment (Simmonds & Keer, 2007), although there is little evidence relating to the success of these interventions (Palmer, Bailey, Barker, Barney, & Elliott, 2014); the reason for this is likely to be the complex individual nature of the condition.…”
Section: Introductionmentioning
confidence: 99%